Оцінка добробуту порушеної екоситеми шляхом підрахунку екосистемних послуг непрямими методами - Дем'янов, Юрій; Безсмертна, Олеся Олексіївна (Київський національний університет імені Тараса Шевченка, 2024)
This work presents preliminary results of assessing the well-being of a disturbed ecosystem using a methodology proposed by Ukrainian researchers. The methodology was developed to assess the damage caused during the Russian-Ukrainian war and can be used for other practical purposes in the future. The methodology is based on dividing the study area into separate biotopes and assessing the environmental services they provide. The National Catalogue of Biotopes of Ukraine was used as a basis for the classification of biotopes. Ecosystem services were classified according to the CICES-UA classifier based on CICES 4.3. The first results obtained will allow us to further deepen the study of the selected territory and identify aspects of practical application of the proposed methodology.
Assessment of the well-being of a disturbed ecosystem by calculating ecosystem services by indirect methods